The Importance of islamic art in mosque interior - Othman, Roslina; Zainal-Abidin, Z.J. (2011)
Mosques, as symbol of Islamic architecture must play an important role in reflecting the superiority of Allah the Almighty. There are many ways in making it successful and one of them is through the high quality of aesthetic value. Aesthetic value in Islamic art and architecture is normally portrayed by the highest degree of motifs and ornamentation. Contemporary mosque designers normally focused on the majestic looks of the exterior part of the mosques and leave the manipulation of the interior space to the users. There are scholars who said that mosques should act as community development centre, some decided on the uniqueness of traditional Malaysian architecture and some believed that mosques must have domes and minarets as symbols of Islamic architecture. This paper realized on the aesthetics and beauty of mosque interior that fulfils the psychological needs of human beings: that is to be inside a beautiful ambience. Ornamentation should be taken as part of mosque components and not as mere decorations done after-thought or filling in the gap. The main objective of the paper is why is it important to focus the ornamentation towards mosque interior so that ornamenting the mosque will not be done uncontrollably and unnecessarily.